ANALISIS KINERJA SIMPANG TAK BERSINYAL JALAN TRANS SULAWESI DENGAN JALAN SISWA KECAMATAN PAGUAT KABUPATEN POHUWATO - Rudi; Putri Lada, Camila (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine the performance of the unsignalized intersection of Jalan Trans Sulawesi with Jalan Siswa, Paguat District, Pohuwato Regency. The study was conducted for three months starting from November 2022 to January 2023 at unsignalized intersections located on Trans Sulawesi Road, Pentadu Village with Siswa Road, Siduan Village, Paguat District, Pohuwato Regency. Data collection was carried out in the morning at 07.00 - 09.00 WITA, afternoon at 11.00 - 13.00 WITA, and evening at 16.00 - 18.00 WITA. From the results of the analysis that has been carried out, the following conclusions can be drawn: 1) unsignalized intersections tend to experience increased traffic density when vehicle volumes are high, especially during peak hours such as office hours and during crowds or market days. 2) the risk of accidents can increase due to a lack of control over vehicle traffic that has the potential for accidents.